Enhancing Fraud Detection and Prevention through Effective Control Environment: A Phenomenological Study: Meningkatkan Deteksi dan Pencegahan Kecurangan melalui Lingkungan Pengendalian yang Efektif: Sebuah Studi Fenomenologi - Hanif, Aisha; Oktaviarini, Dina Dwi; Hanun, Nur Ravita; Ade Prasetya, Atina Nabila; Nadhifah, Binti (Indonesian Journal of Law and Economics Review, 2023)
This research delves into the pivotal role of the control environment as the bedrock of internal control, shaping the organization's culture and structure. By encompassing integrity, ethical values, organizational structure, human resource policies, and management practices, the control environment significantly influences fraud occurrences. This study aims to explore how the control environment contributes to fraud detection and prevention. Employing a qualitative phenomenological approach, the research probes into human perceptions and experiences, shedding light on the intricate interplay between control environment elements and fraud mitigation efforts. The findings provide valuable insights into the practical implications of cultivating a robust control environment to curb fraudulent activities, thereby fostering a more secure and ethically sound organizational ecosystem Highlight: Foundational Importance: This study examines the central role of the control environment in shaping organizational culture and structure, thereby significantly influencing fraud occurrences. Holistic Impact: Encompassing integrity, ethical values, structure, policies, and practices, the control environment's interplay is explored to understand its contribution to fraud detection and prevention. Phenomenological Exploration: Employing a qualitative phenomenological approach, the research delves into human perceptions, shedding light on the intricate relationship between control environment elements and efforts to mitigate fraud. The findings offer practical insights for cultivating a robust control environment that fosters a secure and ethically sound organizational ecosystem. Keyword: Control Environment, Internal Control, Fraud Detection, Prevention, Qualitative Phenomenology